Proximate Composition, Texture Performance and Sensory Evaluation of Lindur Fruit-Potato Simulation Chips Enriched With Shrimp (Penaeus Vannamei) Shell Powder - Diah Ikasari; Ema Hastarini (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2016)
Study aimed to investigate the utilization of shrimp shell powder in the production of lindur fruit-potato simulation chips, which was assessed using proximate composition, texture performance and sensory evaluation parameters. Three different ratios of lindur fruit-potato flour (w/w) (30:70, 40:60 and 50:50), as well as different concentrations of shrimp shell powder (0, 1, 3 and 5%) were used in the formula. The results showed that lindur fruit-potato simulation chips enriched with shrimp shell powder had 3.22-4.42% moisture content, 3.33-4.94% ash content, 3.77-5.83% protein content, 14.59-19.04% fat content, 71.06-76.34% carbohydrate content and 341.4-530.9 g/cm2 hardness. Ratio lindur fruit flour and potato flour of 40:60 as well as 3% of shrimp shell powder was chosen as the best treatment since the formula produced lower hardness, higher protein content and the most crispy and tasty chips preferred by panelists.